KAJIAN YURIDIS PUTUSAN PEMIDANAAN KORUPSI BANSOS COVID-19 DALAM PERSPEKTIF KEADILAN DAN KEPASTIAN HUKUM - Jemmy Satria Nugraha; Syahrul Anwar; Suradi (Integrative Perspectives of Social and Science Journal, 2025)
This article examines Decision Number 29/Pid.Sus-TPK/2021/PN.Jkt.Pst concerning the Covid-19 social assistance corruption case using a normative-juridical approach. The analysis focuses on the fulfillment of offense elements, the application of legal certainty, and the assessment of justice in sentencing. The findings show that the elements of corruption were proven through admissible evidence, thus fulfilling formal legal certainty. However, the court’s reasoning has not fully reflected substantive justice, particularly regarding sentence aggravation during the pandemic and the resulting social harm. The deterrent effect of the sentence also remains questionable given the extraordinary nature of corruption. Therefore, while the decision satisfies legal legality, a more proportional and justice-oriented sentencing approach is still required for corruption cases committed during national crises.